Plasmonic effect of different nanoarchitectures in the efficiency enhancement of polymer based solar cells: A review. (October 2018) - Srivastava, A.; Samajdar, D.P.; Sharma, D.
Highlights: Effect of incorporation of nanoarchitectures in OSCs to improve absorption efficiency. Plasmonic effects such as LSPR, light scattering and surface plasmon polariton exhibited by NPs. Techniques to improve the PCE through alterations in the working mechanism in OSCs. Recent Experimental Results on Nanoarchitecture based OSCs discussed with challenges. Abstract: The cost-effectiveness, ease of fabrication on flexible substrates due to versatility in production methods, ability to tailor the molecular properties according to concerned application are some of the potential advantages offered by organic materials that attracts the attention of the researchers worldwide for their utilisation in Organic Solar Cells (OSCs). OSCs can combine the donor and acceptor materials to provide multiple benefits such as high absorption coefficient, non-toxicity, tuneable band gap and mechanical flexibility. However, due to the amorphous nature of these organic materials and short diffusion length of excitons, the thickness of the active layer of OSCs need to be kept small (∼100 nm) which reduces the number of photons absorbed. The incorporation of 2D and 3D nano-architectures such as nanoparticles, nanospheres, nanodots and nanostars in the active layer, buffer layer and electrodes in OSCs can significantly improve the absorption characteristics through nanoscale light trapping employing Surface Plasmon Resonance Effect and enhance mobility and conductivity by providing continuous charge transport pathways to the electrodes. This review emphasizes the improvements made in different steps in the working of OSCs by insertion of nanostructures and also explores the different challenges at architectural and plasmonic level limiting the PCE of these devices. It also highlights the recent progress and development of OSCs based on metal nanostructures in terms of photovoltaic parameters and the key research areas on which further improvement can be achieved for large scale commercialisation.